DELIK PENODAAN AGAMA ISLAM DI INDONESIA - Nazar Nurdin (International Journal Ihya' 'Ulum al-Din, 2017)
Criminal Law and Article 27-28 of the Law on Information and Electronic Transactions constitute a legal instrument to ensnare a perpetrator of religious blasphemy. This article is a legal research with a normative-empirical approach. The findings indicate that: first, judges' consideration in the case of defamation of Islam contained in the decision Number: 80 / Pid.B / 2015 / PN Bna, Number: 10 / Pid.Sus / 2013 / PN.Pt and Number: 06 / Pid.B / 2011 / PN.TMG is more looking at the impact of criminal acts committed. However, in its implementation the three decisions are not entirely based on the applicable law rules, including the decision based on the provisions in Law No. 1 of 1965 on Prevention and or Defamation of Religion, but adopted an unwritten source of law from the Fatwa of Indonesian Council of Ulama. Another implementation is in the case of religious blasphemy at the community level tended to be followed by very severe punishment to the perpetrators. Secondly, religious blasphemy is not mentioned in detail in Islamic legal literature. If the perpetrators of desecration of a Muslim, Islamic law tend to refer to the perpetrators as kafir. Whereas if the perpetrator is a non-Muslim, one cannot be included in the category of apostasy (riddah). Categorization as a kafir does not necessarily make the Muslims punished jarimah had (hudud). Therefore, punishment takzir can be an alternative punishment that can be applied to the perpetrators of religious blasphemy, both Muslims and non-Muslims---Tindak pidana penodaan agama yang termanifestasikan dalam pasal 156a Kitab Undang-Undang Hukum Pidana dan pasal 27-28 UU Informasi dan Transaksi Elektronik merupakan satu instrumen hukum untuk menjerat seorang pelaku penistaan agama. Artikel ini merupakan penelitian hukum dengan pendekatan normatif-empiris. Hasil temuan menunjukkan bahwa: pertama, pertimbangan majelis hakim dalam perkara penodaan agama Islam yang termuat dalam putusan Nomor: 80/Pid.B/2015/PN Bna, Nomor: 10/Pid.Sus/2013/PN.Pt dan Nomor: 06/Pid.B/2011/PN.TMG lebih melihat kepada dampak yang ditimbulkan dari perbuatan pidana yang dilakukan. Namun dalam implementasinya tiga putusan tidak seluruhnya berlandaskan aturan hukum yang berlaku, termasuk mendasarkan putusan pada ketentuan dalam UU PNPS  Nomor 1 Tahun 1965 tentang Pencegahan dan atau Penodaan Agama, tetapi mengadopsi sumber hukum tidak tertulis dari Fatwa Majelis Ulama Indonesia. Implementasi lainnya ialah dalam kasus penodaan agama yang ramai di tingkat masyarakat cenderung diikuti hukuman amat berat kepada para pelaku. Kedua,penodaan agama tidak disebutkan secara rinci dalam literatur hukum Islam. Jika pelaku penodaan seorang Muslim, hukum Islam cenderung menyebut pelaku sebagai kafir. Sementara jika pelaku seorang non-Muslim, seorang tidak bisa dimasukkan ke dalam kategori murtad (riddah). Kategorisasi sebagai kafir tidak lantas menjadikan Muslim dihukum jarimah had (hudud). Oleh karena itu, pidana takzir bisa menjadi hukuman alternatif yang bisa diterapkan kepada para pelaku penodaan agama, baik Muslim maupun non-Muslim